Sample type is vital for diagnosing infection with peste des petits ruminants virus by reverse transcription PCR - Luka, Pam Dachung (The Korean Society of Veterinary Science, 2012)
Peste des petits ruminants (PPR) diagnosis from suspected samples from sheep and goats was carried out. Buffy coat, tissues, and oculo-nasal swabs were analyzed using nucleoprotein (NP3/NP4) and fusion protein (F1/F2) gene primers, respectively. Analysis of the sample types and primer set revealed that buffy coat are the best type of samples for PPR diagnosis and the use of two set of primers will increase the number of positives.